Capital Structure, Company Size and Profitability Influence on Company Value with Managerial Ownership as Moderation Variables - Ikhwan Ari Wibowo; Dwi Asih Surjandari (International Journal of Social Service and Research (IJSSR), 2023)
The results of this study look for the relationship between the influence of managerial ownership as a moderating variable between the independent variables, namely capital structure, firm size and profitability on the dependent variable, namely firm value. Population in manufacturing companies listed on the IDX in 2015-2020. The method of selecting the sample by purposive sampling is 65 companies and the number of observations is 390 units of observation. This study uses panel data regression analysis. In the goodness of fit analysis test the results have an effect together and the t parameter test results that have a positive effect on firm value are capital structure and profitability. While that has a negative effect on the value of the company is the size of the company. The existence of a moderating variable, namely managerial ownership in the relationship between capital structure and firm value has a positive effect, firm size has no effect on firm value and profitability has a negative effect on firm value.